Liver transplantation for alcoholic hepatitis in the United States: Excellent outcomes with profound temporal and geographic variation in frequency. Issue 3 (13th August 2020) - Cotter, Thomas G.; Sandıkçı, Burhaneddin; Paul, Sonali; Gampa, Anuhya; Wang, Jennifer; Te, Helen; Pillai, Anjana; Reddy, Kapuluru G.; di Sabato, Diego; Little, Ester C.; Sundaram, Vinay; Fung, John; et al.
Abstract : Medical‐refractory severe alcoholic hepatitis (AH) has a high mortality. The national frequency, longer term outcomes and regional practices of AH liver transplantation (LT) in the United States are not well described, despite the increasing mortality from alcohol‐associated liver disease. We analyzed the trends in frequency and outcomes of UNOS data on 39 455 adult patients who underwent LT from 2014 to 2019, including AH LT recipients. LTs for AH increased 5‐fold, from 28 in 2014 to 138 in 2019, varying 8‐fold between UNOS regions. Three transplant centers accounted for 50%‐90% of AH LTs within each region. The number of transplant centers performing AH LTs increased from 14 in 2014 to 47 in 2019. AH patients were younger (mean = 39.4 years), had higher MELD scores (mean = 36.8), and were more often on dialysis (46.0%) and in ICU (38.4%), compared to other indications (all P < .05). One‐ and 5‐year graft survivals for AH LT recipients were 91.7% and 81.9%, respectively. The frequency of AH LT is increasing rapidly, with excellent medium‐term outcomes. An impact of AH recurrence on patient or graft survival is not apparent in this national analysis. There are marked geographic variations in practices, highlighting the lack of selection criteria standardization. Abstract : This analysis of the US national transplant database shows that liver transplantation for alcoholic hepatitis has dramatically increased in recent years with excellent outcomes despite profound geographic variation in this practice. See the editorial from Maddur and Asrani on page 921 .